Adultez emergente e significado do trabalho na transição universidade-mercado - Souto, Juliana Maia (2020)
The transformations in working world and its precarious conditions about the existence and labor activity has affected, especially, youg adults in their educational and labor paths, and in their process to become adulthood. The difficulty of this group in assuming the adulthood status and accomplish their life project has caused differents dynamics in youth trajectories, characterized by unpredictability and fragemented paths. In this way, to investigates this complex and dynamic life’s period, some researches are concerned with the goal about analyzing the trajectories of youth in the transformations, based on educational work paths. Among this theories, the Emergin Adulthood has gained prominence, considerig the goal of analyze the psychological and objective aspects of this period of live. In this context of uncertains and minimun public policies for young people, it has become important to identify how the meanigs about the changes of working world have influenced the development youth trajectories. Therefore, our goal is to investigate the meanings attributed to working during tha transition to adulthood and its relation with the phenomenon of emerging adultood. This is a quantitative research, that was aimed at young people in transition “university-labor market” in the last year of graduation and recent graduates aged between 18 and 29 years. In total, 272 young people answeared a personal and social survey, an ESAT-BR and IDEA-BR. The results demonstrated a possible relation between the dimensions of emerging adulthood and the meaninngs of work, idicating that youg people perceive work as an importante resource to deal with the transition to adulthood. Furthermore, the association between sociodemographic variables and the investigates constructs showed that other factors are related to these phenomenon, explained by it complexity.